1997
DOI: 10.33584/jnzg.1997.59.2256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nitrate fertilisers as nitrogen sources for spring pasture

Abstract: Since 1994 Ravensdown have carried out a series of pastoral trials in South Canterbury, aimed at looking at the relative effectiveness of different forms of nitrogen in the spring. These trials showed that in general those N products containing some nitrate-N (i.e., calcium ammonium nitrate - CAN, and ammonium sulphate nitrate - ASN) could be more effective than urea and ammonium sulphate when soil temperatures were low. However, responses were inconsistent because of spring climatic conditions. In 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…CAN and ASN (containing nitrate-N) gave higher pasture responses than AS (containing ammonium-N) and urea. Nitrate-N gave the best response when applied at soil temperature of 3-5 o C. Craighead et al [63] further suggested that winter-active grasses (i.e. short-rotation ryegrass) could give a larger response to nitrate-N during early spring.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…CAN and ASN (containing nitrate-N) gave higher pasture responses than AS (containing ammonium-N) and urea. Nitrate-N gave the best response when applied at soil temperature of 3-5 o C. Craighead et al [63] further suggested that winter-active grasses (i.e. short-rotation ryegrass) could give a larger response to nitrate-N during early spring.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Soil microbes are involved in the hydrolysis and nitrification of urea-N. It would be expected that low temperature limits plant responses to urea [63].…”
Section: Environmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reduces the amount of autumn nitrogen required (such as used in 1995) to boost a marginal feed supply. Nitrogen fertilisers containing nitrate nitrogen were preferred for late autumn and winter nitrogen applications, since ongoing work on the farm showed these were more reliable than urea at cool soil temperatures (below 6°C) (Craighead et al 1997).…”
Section: Autumn Feed Supply and Seed Yieldmentioning
confidence: 99%